Value relevance in assessing the quality of financial reports: A systematic literature review - Achmad Farid Dedyansyah; Maria Arista Ulfa (Journal of Enterprise and Development (JED), 2023)
Purpose — The purpose of this research is to identify trends in capital market publications across different scientific fields, such as economics, finance, and accounting. The focus is on exploring value relevance research for assessing the performance of company financial statements.Method — This study employs a systematic literature review method to identify and analyze trends in value relevance research over the past 9 years, gathered from the Emerald Group and Science Direct databases. The research dataset consists of 31 articles, all of which underwent bibliometric and content analysis.Result — We discovered that the majority of value relevance research in the Asian region was concentrated in China. The theoretical framework employed was valuation theory, complemented by the methodological approach of ordinary least squares. The type of value relevance investigated was relative association study. This classification has significant potential for future research utilization. The results indicate that investors are willing to invest in companies located in the Asian region based on assessments of the value relevance of their financial statements.Contribution — This research makes a comprehensive academic contribution to the future trend of value relevance publications, particularly within the field of economic and investment research in Southeast Asia. The methodology employed in this study is the systematic literature review, a method rarely utilized for examining financial statements through the lens of value relevance.